Transformasi Kesadaran Lingkungan Melalui Pendampingan Media Digital Berbasis Kearifan Lokal Bagi Guru SD Ngadipuro 03 - Surayanah; Esti Untari; Dhiya Nasywa; Febri Dwi Asmawan; Dina Nur Abidah (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Teachers’ limited understanding of how to utilize digital media based on local wisdom results in learning that is not sufficiently contextual and is not yet optimal in fostering environmental awareness among students. This community service activity aims to improve the understanding of teachers at SDN Ngadipuro 03 in utilizing the “Sahabat Lingkungan” digital media—based on the local wisdom of Wonotirto Subdistrict—as a learning resource. The methods used included technical guidance, media usage training, practical exercises, and implementation support in the classroom. Evaluation was conducted through pre-tests and post-tests to measure improvements in teachers’ understanding. The results showed an increase in the average pre-test score from 85,63% to 93,34% on the post-test. In addition to enhancing teachers’ understanding, the “Sahabat Lingkungan” digital media provides a more interactive and contextual learning alternative that is easily integrated with local resources, thereby supporting the strengthening of environmental awareness in elementary schools. Thus, guidance on the use of digital media based on local wisdom has proven effective in improving teachers’ competencies while supporting more meaningful learning experiences.